Indicators of psychological distress and body image disorders in female patients with breast cancer - Helena van Oers; Lourens Schlebusch (Journal of Mind and Medical Sciences)
Breast cancer patients are vulnerable to elevated stress related to receiving the diagnosis, unfamiliar and invasive treatment, and coping with the side-effects of treatment, which may find various forms of expression. Another common feature of this patient population is body image dysphoria. Both the disease and treatment lead to impairments in physical appearance and general bodily functioning. This study aimed to explore the differential manifestations of stress and the nature of body image dysphoria within a sample of female breast cancer patients (n=80), compared to female patients with other sites of disease (n=80) in order to examine differences in the experiences of distress in these groups. Patients completed 4 questionnaires relating to psychological distress and body image dysphoria. The results showed the breast patients reported significantly higher levels of body image dysphoria and reflected differential indicators of stress, namely more psychological and behavioral expression, as compared to the other group.